ABOUT PROBLEMS OF PERFECTION OF LANGUAGE OF LEGISLATIVE ACTS - Abdreeva, Мағия Әбдірейқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The orticle discusses the problem questions arising up during translation of normatively-legal acts